Impact assessment of corporate income tax nullification: case of Armenia - O. A. Patvakanian (Стратегические решения и риск-менеджмент, 2017)
Armenian economy currently experiences a range of fundamental challenges which require institutional solutions. Loans for businesses are allocated under unfavourable conditions as compared with other countries. In the given circumstances, tax incentives are one of the most important elements to ensure economic growth. One of such a tax incentives is abolishment of corporate income tax on retained earnings. The given reform has resulted in substantial economic results in Estonia in the year of 2000. Current contribution poses a comparative study of Estonia’s economy in 2000 (the year of reform) and Armenia’s economy as of now (assuming the reform might take place next year). At the same time, the paper assess the macroeconomic impact of corporate income tax nullification.